2022
DOI: 10.14715/cmb/2021.67.4.18
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Siglec-G ITIM domain during bacterial infection

Abstract: Siglecs, membrane-bound lectins of the sialic acid-binding immunoglobulin superfamily, inhibit immune responses by recruiting tyrosine phosphatases (e.g., SHP-1 and SHP-2) through their cytoplasmic immunoreceptor tyrosine-based inhibition motif (ITIM) domain. The role of Siglecs in infection has been extensively studied, but downstream signaling through the ITIM domain remains unclear. Here, we used a GST pull-down assay to identify additional proteins associated with the ITIM domain during bacterial infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Recently, the authors demonstrated that Rab1a bound to the ITIM domain of Siglec-G under normal homeostasis. By contrast, Rab1a was recruited to the ITIM domain during bacterial infection, suggesting that GDI2 and Rab1a may regulate immune response through interaction with the ITIM domain during bacterial infection ( 18 ). In the present study, to investigate whether Rab1a plays a role during bacterial infection, WT and Rab1a +/− mice were challenged with 10 mg/kg LPS and collected serum from the mice as previously described ( 21 , 22 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the authors demonstrated that Rab1a bound to the ITIM domain of Siglec-G under normal homeostasis. By contrast, Rab1a was recruited to the ITIM domain during bacterial infection, suggesting that GDI2 and Rab1a may regulate immune response through interaction with the ITIM domain during bacterial infection ( 18 ). In the present study, to investigate whether Rab1a plays a role during bacterial infection, WT and Rab1a +/− mice were challenged with 10 mg/kg LPS and collected serum from the mice as previously described ( 21 , 22 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors have previously demonstrated that Rab1a may regulate the immune response through interaction with the ITIM domain during bacterial infection in vitro ( 18 ). To further investigate the function of Rab1a in vivo , the present study generated mice with a trapped Rab1a gene and uncovered a novel role for Rab1a during early embryonic development in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on the inflammatory mechanism of cerebral aneurysm has revealed that inflammatory cells infiltrate and destroy the elastic and collagen fibers of the cerebral artery wall, resulting in the disease's progression. The main cells involved are macrophages, where monocyte chemotactic protein-1 (MCP-1) regulates the expression of pro-inflammatory genes such as MCP-1, and nuclear factor-xb (NF-B), which transcriptionally regulates the expression of pro-inflammatory genes the same as MCP-1, and matrix metalloproteinases (MMPs), particularly MMP-9, are abnormally highly expressed [9]. NF-κB is involved in the inflammatory response and plays a regulatory role.…”
Section: Major Mechanism Of Ca: Inflammationmentioning
confidence: 99%